2016
DOI: 10.18052/www.scipress.com/ilshs.68.7
|View full text |Cite
|
Sign up to set email alerts
|

Sri Lanka’s General Election 2015

Abstract: Sri Lanka emerges from this latest election with a hung Parliament in 2015. A coalition called the United National Front for Good Governance (UNFGG) won 106 seats and secured ten out of 22 electoral districts, including Colombo to obtain the largest block of seats at the parliamentary polls, though it couldn't secure a simple majority in 225-member parliament. It also has the backing of smaller parties that support its agenda of electoral. In the August parliamentary election, the former president Rajapaksa fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The election of President Sirisena in 2015 showed that Sri Lanka can make a peaceful political transition (Aliff, 2016; Nelson, 2015), but sustainable peace-building and the development of a democratic, pluralist political economy is a major challenge. The government has responded to pressure exerted by the international community to independently investigate alleged war crimes during the final days of the war (Manikkalingam, 2016).…”
Section: Sri Lanka Since 2015mentioning
confidence: 99%
“…The election of President Sirisena in 2015 showed that Sri Lanka can make a peaceful political transition (Aliff, 2016; Nelson, 2015), but sustainable peace-building and the development of a democratic, pluralist political economy is a major challenge. The government has responded to pressure exerted by the international community to independently investigate alleged war crimes during the final days of the war (Manikkalingam, 2016).…”
Section: Sri Lanka Since 2015mentioning
confidence: 99%